Pengaruh Persepsi Kemudahan, Kegunaan, dan Kredibilitas terhadap Kepuasan dan Loyalitas Pengguna E-Wallet Dana - Abdul Aziz Apriyanda; Harti Harti (Jurnal Pemasaran Kompetitif, 2022)
The purpose of this study was to determine the effect of perceived ease, usability and credibility and the role of consumer satisfaction on the loyalty of Dana E-wallet users. The type of research used is descriptive quantitative research. The type of data in this study is quantitative data. Then the source of this research data is the primary data source. the population is all Dana E-wallet users who have used the application more than once. in the study obtained 130 respondents with sampling using non-probability with purposive sampling technique. Collecting data in this study using a questionnaire with a Likert scale through google form media. Using data analysis techniques SEM (Structural Equation Modelling) with PLS (Partial Least Square) with the stages of Evaluation of measurement model and Evaluation of structural model. The results of this study are consumer satisfaction can play a full role or full mediation in mediating the influence between perceived convenience and consumer loyalty, consumer satisfaction does not mediate the influence between perceived usefulness and consumer loyalty, consumer satisfaction does not play a full role in mediating the influence between perceived convenience and consumer loyalty.